Aggregate and household demand for money : evidence from public opinion survey on household financial assets and liabilities / Hiroshi Fujiki and Cheng Hsiao. - Fujiki, Hiroshi, 1964- (IMES discussion paper series, 2008)
We use data from Public Opinion Surveys on Household Financial Assets and Liabilities from 1991 to 2002 to investigate the issues of unobserved heterogeneity among cross-sectional units and stability of Japanese aggregate money demand function. Conditions that permit individual data and aggregate data to be modeled under one consistent format are given. Alternative definitions of money are explored through year-by-year cross-sectional estimates of Fujiki-Mulligan (1996) household money demand model. We find that using M3 appears to be broadly consistent with time series estimates using the aggregates constructed from the micro data. The results appear to support the existence of a stable money demand function for Japan. The estimated income elasticity for M3 is about 0.68 and five year bond interest rate elasticity is about -0.124.--Author's description.